Effect of educational intervention on attitudes toward the concept of criminal responsibility - Shiina, Akihiro (World J Psychiatry, 2017)
AIM: To evaluate the effect of educational intervention on individuals’ knowledge of and attitudes toward forensic mental health. METHODS: We conducted a questionnaire regarding attitudes toward various ideas about forensic mental health. The respondents attended a 1-h seminar regarding forensic mental health after answering the questionnaire. On completion of the seminar, the respondents answered another questionnaire containing many of the same questions as contained in the pre-seminar questionnaire. RESULTS: A total of 86 individuals attended the seminar, and 78 responded to the questionnaire. Only 13 (18.8%) participants were supportive of the concept of criminal responsibility initially, and there was a statistically significant increase in those who became more supportive after the seminar, with 22 (33%) being supportive after the seminar (Wilcoxon signed-rank test, P < 0.001). Logistic regression analysis revealed that participants who were skeptical about forensic mental systems and those with fewer opportunities to see media reports regarding psychiatry were likely to become supportive of criminal responsibility after the intervention. CONCLUSION: These results suggest that public attitudes toward criminal responsibility and mental health can be influenced via educational interventions.